Faktor-Faktor yang Berhubungan Dengan Stres Keluarga dalam Merawat Penderita Diabetes Mellitus Tipe II Tahun 2025 - Eko Sujadna; Ardiansyah Ardiansyah; Arjuna Arjuna (JURNAL KESEHATAN TERAPAN, 2026)
Family stress is a psychological response that arises due to the burden of caring for a family member with a chronic illness such as Type II Diabetes Mellitus (DM). Based on medical records from Sekar Biru Public Health Center in 2024, there were 98 cases of Type II DM, mostly managed at home by family caregivers. This study aimed to identify factors associated with family stress in caring for Type II DM patients in Sekar Biru Village in 2025. A quantitative study with a cross-sectional design was conducted using total sampling, involving 98 family caregivers. Data were analyzed using univariate and bivariate methods with the Chi-Square test. The results revealed five variables significantly associated with family stress: financial burden (ρ = 0.000), knowledge level (ρ = 0.000), duration of illness (ρ = 0.000), employment status (ρ = 0.012), and presence of complications (ρ = 0.038). In conclusion, financial constraints, lack of knowledge, prolonged illness duration, unemployment, and diabetes complications significantly influence caregiver stress levels. Health education is essential to increase family understanding of diabetes management. Furthermore, public health centers should strengthen family-oriented health promotion to reduce caregiver burden. This research may serve as a reference for health workers, educational institutions, and future studies exploring broader aspects of caregiver well-being.